A Multidimensional Model of Planned Behavior Theory and Its Prediction on Entrepreneurial Intention - Mukhammad Kholid Mawardi; Sujarwoto Sujarwoto; Rindi Ardika Melsalasa Sahputri (MIX: JURNAL ILMIAH MANAJEMEN, 2022)
It is widely believed that entrepreneurial intention is a central concept within entrepreneurial education. Students who have entrepreneurial intentions tend to be self-employed and were not likely to be job seekers. Therefore, in the domain of entrepreneurial research, entrepreneurial intention is a critical issue in studying entrepreneurship.Objectives: The study examines the multidimensional model of theory of planned behavior and its prediction on entrepreneurial intention among university students. The premise of this theory is that individual attitude and behavior are complex processes in which multiple factors determine effectiveness. This study investigates whether this theory will be best described with a multidimensional construct or a single construct and how the relationship path of each dimension.Methodology: The study used a cross-sectional design. Data was distributed to 583 university students in the vocational program at Brawijaya University Indonesia. Data was analyzed using multi-group structural equation modeling in two steps: measurement model test and structural model test. The measurement model was used to test and validated the instrument at the latent variable level while Confirmatory Factor Analysis (CFA) was used to test the model.Finding: The study found entrepreneurial intention was established by a continuum construct: choice intention, commitment to entrepreneurship, and nascent entrepreneurship. Attitude toward entrepreneurship consists of two dimensions, affective and instrumental attitude. Perceived behavioral control comprises of self-efficacy and perceived controllability. Every dimension of entrepreneurial intention has a different relationship with the dimensions of attitude and perceived behavioral control with self-efficacy and affective attitude as the stronger predictor of entrepreneurial intention than instrumental attitude and perceived controllability. The association of choice intention on commitment and the effect of commitment on nascent entrepreneurship is larger among males rather than females.Conclusion: The study answered the necessity to conduct and test an empirical model of the multidimensional construct of planned behavior theory and entrepreneurship intention. By treating the model as multiple models, we proposed a new perspective of the best model that describes entrepreneurial behavior. Using structural equation modeling, this study reveals the different relationship paths of each dimension.